PP.33.05: CLUSTERING OF CARDIOMETABOLIC RISK FACTORS TO HIGH BLOOD PRESSURE IN OBESE YOUTH. (June 2015) - Alvarez, J.; Torro, M.I.; Aguilar, F.; Redon, P.; Lurbe, E.
Abstract : Objective: Obesity in childhood has been shown to increase the risk of cardiometabolic disease. Identification of obese youth with cardiometabolic components may define a high-risk group within the obese child population. The objective was to assess the prevalence of the cardiometabolic risk factors in obese youth. Design and method: Six hundred and eleven obese Caucasians of both sexes (270 females), of European origin, from 6 to 18 years of age (mean age 11.3 2.4) were included. Obesity was defined as higher than or equal to 95th percentile for age and sex. The subjects were qualified as normotensive or high blood pressure (BP) according to the ESH office BP criteria (Lurbe et al, 2009). Fasting blood was obtained and glucose, insulin, and lipid profile, were assessed. Hyperinsulinism was defined from norms for pubertal stage. Abnormal fasting lipids were defined from normative data (Daniels et al, 2008). Results: Moderate obesity was present in 86% and there were no sex differences in mean BMI z-score. From the total population, 354 (57.8%) had at least one cardiometabolic risk factor in addition to obesity. The prevalence of cardiometabolic risk factors were: 235 subjects (39%) with one risk factor, 101 subjects (16.5%) with two factors, 17 subjects (2.8%) with three, and one subject had four components (0.2%). There were no significant differences in the prevalence between males and females. Among all the risk factors the most prevalent was hyperinsulinism (30.8%), followed by lipid abnormalities (12.9%), and high BP (10.5%). High BP was associated with hyperinsulinism in 10%, with lipid abnormalities in 8%, and with both hyperinsulinism and lipid abnormalities in 0.6%. Figure. No caption available. Conclusions: The presence in more than half of the obese population of at least one cardiometabolic risk factor stresses the importance of adiposity. High BP is frequently associated with one or more cardiometabolic risk factor.